HIV testing barriers and intervention strategies among men, transgender women, female sex workers and incarcerated persons in the Caribbean: a systematic review. (10th September 2019) - Hamilton, Akeen; Shin, Stephen; Taggart, Tamara; Whembolua, Guy-Lucien; Martin, Indira; Budhwani, Henna; Conserve, Donaldson
Abstract : Background: This systematic review summarises evidence on the HIV testing barriers and intervention strategies among Caribbean populations and provides pertinent implications for future research endeavours designed to increase rates of HIV testing in the region. Methods: We used a systematic approach to survey all literature published between January 2008 and November 2018 using four electronic databases (MEDLINE/PubMed, Embase, Web of Science and Global Health). Only peer-reviewed articles published in English that examined HIV testing uptake and interventions in the Caribbean with men, men who have sex with men, female sex workers, transgender women and incarcerated individuals were included. Results: Twenty-one studies met the inclusion criteria. Lack of confidentiality, access to testing sites, stigma, discrimination, poverty and low HIV risk perception were identified as key barriers to HIV testing. These barriers often contributed to late HIV testing and were associated with delayed treatment initiation and decreased survival rate. Intervention strategies to address these barriers included offering rapid HIV testing at clinics and HIV testing outreach by trained providers and peers. Conclusion: HIV testing rates remain unacceptably low across the Caribbean for several reasons, including stigma and discrimination. Future HIV testing interventions should target places where at-risk populations congregate, train laypersons to conduct rapid tests and consider using oral fluid HIV self-testing, which allows individuals to test at home.